The Will to Improve : Governmentality, Development, and the Practice of Politics - Li, Tania, 1959- (Book collections on Project MUSE., 2007)
The Will to Improve is a remarkable account of development in action. Focusing on attempts to improve landscapes and livelihoods in Indonesia, Tania Murray Li carefully exposes the practices that enable experts to diagnose problems and devise interventions, and the agency of people whose conduct is targeted for reform. Deftly integrating theory, ethnography, and history, she illuminates the work of colonial officials and missionaries; specialists in agriculture, hygiene, and credit; and political activists with their own schemes for guiding villagers toward better ways of life. She examines donor-funded initiatives that seek to integrate conservation with development through the participation of communities, and a one-billion-dollar program designed by the World Bank to optimize the social capital of villagers, inculcate new habits of competition and choice, and remake society from the bottom up. Demonstrating that the "will to improve" has a long and troubled history, Li identifies enduring continuities from the colonial period to the present. She explores the tools experts have used to set the conditions for reform - tools that combine the reshaping of desires with applications of force. Attending in detail to the highlands of Sulawesi, she shows how a series of interventions entangled with one another and tracks their results, ranging from wealth to famine, from compliance to political mobilization, and from new solidarities to oppositional identities and violent attack